2010
DOI: 10.1128/jvi.01550-09
|View full text |Cite
|
Sign up to set email alerts
|

Viral Oncolysis That Targets Raf-1 Signaling Control of Nuclear Transport

Abstract: The central role of Raf protein kinase isoforms in human cancer demands specific anti-Raf therapeutic inhibitors. Parvoviruses are currently used in experimental cancer therapy due to their natural oncotropism and lytic life cycle. In searching for mechanisms underlying parvovirus oncolysis, we found that trimers of the major structural protein (VP) of the parvovirus minute virus of mice (MVM), which have to be imported into the nucleus for capsid assembly, undergo phosphorylation by the Raf-1 kinase. Purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 79 publications
1
66
0
Order By: Relevance
“…Like for other viruses, it has been shown that parvoviruses have functional NLSs in their capsid proteins (32,57). It has been demonstrated that these NLSs are necessary for nuclear import of capsid protein trimers prior to virion assembly in the nucleus (44) and that nuclear import of capsid protein trimers is dependent on phosphorylation by Raf-1 (45). One of the parvovirus NLSs, within VP2, is buried inside the capsid of assembled virions and could not be involved in nuclear entry of the incoming capsid during initial infection (1,31).…”
Section: Discussionmentioning
confidence: 99%
“…Like for other viruses, it has been shown that parvoviruses have functional NLSs in their capsid proteins (32,57). It has been demonstrated that these NLSs are necessary for nuclear import of capsid protein trimers prior to virion assembly in the nucleus (44) and that nuclear import of capsid protein trimers is dependent on phosphorylation by Raf-1 (45). One of the parvovirus NLSs, within VP2, is buried inside the capsid of assembled virions and could not be involved in nuclear entry of the incoming capsid during initial infection (1,31).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in rat C6 and human U373MG glioblastoma cells infected with MVM, the characteristic pattern of VP phosphorylation by Raf-1 was conserved, correlating with a high activity of the MAPK signaling pathway (Riolobos et al 2010). Moreover these glioblastomas were efficiently killed by MVM and the virus underwent productive maturation to high yields (Rubio et al 2001).…”
Section: Parvovirus Capsid Assembly Targets Deregulated Raf Signalingmentioning
confidence: 89%
“…Inside the nucleus the fully assembled icosahedral capsid harbors the NLS and NLM facing to the particle inward. Abbreviations: NPC, nuclear pore complex; NLM, nuclear localization motif; NLS, nuclear localization sequence (based on Lombardo et al 2000;Maroto et al 2000;Riolobos et al 2006;Riolobos et al 2010). …”
Section: Parvovirus Capsid Assembly Targets Deregulated Raf Signalingmentioning
confidence: 99%
See 2 more Smart Citations